QUALITY BY DESIGN APPROACH TO STABILITY-INDICATING REVERSE-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD DEVELOPMENT, OPTIMIZATION, AND VALIDATION FOR THE ESTIMATION OF SIMEPREVIR IN BULK DRUG: - VANITHA C; SATYANARAYANA SV; BHASKAR REDDY K (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: A simple, robust, precise, and selective stability-indicating liquid chromatography (LC) method (reverse-phase high-performance LC) was developed for the estimation of simeprevir through quality by design paradigm. Methods: The chromatographic separation was performed on Water’s 2695(Alliance) equipped with a photodiode array detector at 300 nm. The method was developed on Discovery C18 column (250×4.6, 5 mm) using orthophosphoric acid and acetonitrile (55:45 % v/v) with the flow rate of 1 ml/min at 30°C. The degradation studies of simeprevir were carried out under the stress conditions of hydrolysis (acid, base, and neutral), oxidation, photolytic, and thermal as per the International Conference on Harmonization (ICH) guidelines. The peroxide hydrolysis shows more critical impurities which were well resolved from pure drug with the application of design of experiment and optimized the method. Results: Independent variables (critical analytical attributes) selected for the method optimization were mobile phase ratio, flow rate, and temperature of the column based on the risk assessment. The retention time and resolution were selected as the method response. In response surface method, the central composite design and 23 factorial designs were employed for the optimization of the method. The polynomial equation was derived for the estimation of method response. Conclusion: The method was optimized for better resolution among the drug, and impurity peaks were then validated as per the ICH parameters.